Medieval studies in Zacatecas, Mexico : ten years of work in the Zacatecan Association of Classical and Medieval Studies (AZECME) (Estudios de Historia de España, 2021)
This contribution stems from the concerns raised in the II International Symposium The Middle Ages view other horizons: theoretical and methodological problems, National University of Mar del Plata, Argentina, 2015, together with a simple but nurtured overall balance of academic, dissemination and research conducted ten years of existence the AZECME, as relevant humanistic group with regard to the reflection of other cultures —especially the history of the Middle Ages— being part of an important national reference, if we remember that in the Mexican Republic only in the cities of Puebla, Queretaro and Mexico, there are universities, educational institutions, schools, associations or companies that provide in their curricula training in Classical Antiquity, the Middle Ages or Latin and Greek Languages.
Keywords: Middle Ages; Medieval Studies; Medieval Associations in Mexico